EFFECT OF BREWING BHEE FRUIT POWDER (Melastoma sp) AGAINST THE WEIGHT OF DIABETIC MICE - Rinawati; Sri Wahyuni Muhsin; Siti Maisyaroh Fitri Siregar (PT. Radja Intercontinental Publishing, 2025)
Diabetes is a metabolic syndrome that causes hyperglycemia. Diabetes can lead to weight loss. Glucose level control can indirectly restore weight. Glucose levels can be controlled using synthetic drugs and herbal drugs. Bhee fruit (Melastoma sp) is an herbaceous plant with antidiabetic effects. This study aims to determine the effect of Bhee fruit (Melastoma sp) infusion on weight changes in diabetic mice. The research method was a laboratory experiment using 24 mice which were divided into 6 treatment groups and four replicates, namely normal control, drug control, diabetes control, Treatment 1 (dose 100 mg/kgBB), Treatment 2 (dose 200 mg/kgBB) and treatment 3 (dose 400 mg/kgBB). The results showed that the weight in normal control increased slowly. The diabetes control group experienced weight loss until the last week of observation. The drug control group experienced a weight gain of 31.25%. Weight gain in the treatment group reached 6% (P1), 14.87% (P2), and 25% (P3). Conclusion: The higher the dose, the higher the ability to help restore body weight.